Strontium ranelate reduces duration of consolidation phase in distraction osteogenesis: 2 case reports - Subramaniam, Kishan Rao; Mor Japar Khan, Ed Simor Khan; Zulkifly, Ahmad Hafiz; Sood, Ashwini (Crimson Publishers, 2018)
Distraction osteogenesis a debilitating and time consuming procedure in orthopedics. The common indications for distraction osteogenesis are open fractures, non union and bone resection due to chronic osteomyelitis or large bone loss at initial time of trauma. It is often a limb salvage procedure but also has a role in cosmetic lengthening in short statures. In distraction osteogenesis, there are 3 main phases; latent phase, distraction phase and consolidation phase. Often, patient has to be on external fixator (eg: ilizarov, LRS) for the entire duration of the distraction osteogenesis until clinical union is achieved (frame time). Prolonged external fixation is uncomfortable for the patient and is associated with many complications. Strontium ranelate is widely used in treatment of osteoporosis and to prevent fractures in elderly population. It has dual action and it promotes osteoblastic activity and inhibits osteoclastic activities in bone cells. From our cases, we have found that strontium ranelate given to patients at the end of distraction phase of distraction osteogenesis have significantly reduced the duration of consolidation phase, thus shortening the duration of the patients on external fixator (frame time). Strontium ranelate is a cost effective and non invasive alternative and can be used to reduce patients’ suffering, improve patients’ compliance and reduce the disability period. However, further evaluation of the safety profile of the drug needs to be taken into consideration.